Specialized pro-resolving lipid mediators regulate inflammatory macrophages: A paradigm shift from antibiotics to immunotherapy for mitigating COVID-19 pandemic - Kumar, Vikram; Yasmeen, Nusrath; Chaudhary, Anis Ahmad; Alawam, Abdullah S.; Al-Zharani, Mohammed; Suliman Basher, Nosiba; Harikrishnan, S.; Goud, Muddapuram Deeksha; Pandey, Aishwarya; Lakhawat, Sudarshan Singh; Sharma, Pushpender Kumar (Frontiers in Molecular Biosciences, 2023)
Cytokine storm is one of the macrophage-derived inflammatory responses, which is accountable for the production of various pro-inflammatory cytokines, e.g., interleukin (IL)-1, IL-2, and tumor necrosis factor (TNF)- α at a much higher rate than normal causing pulmonary oedema, acute respiratory distress, and multi-organ failure. The consecutive progression to inflammation, oedema and cytokine storm is triggered by binding of Virus particles to ACE2 receptors of alveolar macrophages. Cytokine storm was one of the causes of the high mortality rate during the Covid-19 pandemic. The basis of cytokine storm is imbalanced switching between an inflammation increasing - pro-inflammatory(M1) and an inflammation regulating- anti-inflammatory(M2) forms of alveolar macrophages which further deteriorates if opportunistic secondary bacterial infections also prevail in lungs. Although antibiotics have been aggressively used during Covid pandemic indiscriminately to mitigate secondary bacterial infections, it has led to the unwarranted development of multidrug resistance (MDR) among the population across the globe. Specialized pro-resolving mediators (SPMs) are generated from the stereoselective enzymatic conversions of essential fatty acids that serve as immune resolvents in controlling acute inflammatory responses. SPMs facilitate the clearance of injured tissue and cell debris, the removal of pathogens, and augment the concentration of anti-inflammatory lipid mediators. The SPMs, e.g., lipoxins, protectins, and resolvins have been implicated in exerting inhibitory influence on with cytokine storm. Therefore, in this review potential roles of SPMs in triggering immunological functions of macrophages and controlling macrophage-derived inflammatory responses are enumerated.